(1259) Economic Integration and foreign trade the case of CMEA التكامل الاقتصادي والتجارة الخارجية: حالة مجلس التعاون الاقتصادي والبيئي - Grote, Gerhard (The Institute Of National Planning., 2018)
Increasing internationalization of the economic life is one of the phenomena of the economic development in the second half of this century; growth rates of foreign trade, exceeding by far growth rates of national income and industrial and agricultural production.